A study on the density of golden apple snail (Pomacea canaliculata) in selected and unmanaged rice paddies in Brgy. Doña Feliza Mejia, Ormoc City, Leyte - Monte, Ed Christian D. (2022)
Golden Apple Snails (Pomacea canaliculata) are an invasive species of snails. Native to Central America, these snails were brought to different parts of the world and now have become agricultural pests. Golden Apple Snails have brought a collective millions worth of damage to rice farms. In Ormoc City, no data is available regarding the Golden Apple Snail population in the local rice fields. Rice fields of Brgy. Doña Feliza Mejia were used as sampling sites. Within a 12-week period, P. canaliculata density, length frequency, and count per 1x1-m quadrat was observed in 24 total quadrats from 3 rice paddies. The average highest density was found to be at week 2, with an average density of 2.08 meters squared. Snail density slowly declined within the succeeding weeks. The lowest density was recorded at week 10 with an average density of 0.42 meters square. Friedman's Two-Way Analysis of Variance for Related Samples (alpha=0.05) was done to compare snail densities over the 12-week sampling periods. The test shows a p-value of 0.005, rejecting the null hypothesis, suggesting that the distribution of snail density in the 12 sampling points are not uniform and the same. The most frequent length interval were snails that measured between 30-40 mm which had a count of 62 individuals. Studies dictate that P. canaliculata at these lengths are mature types.